Pelatihan Aplikasi Smart PLS untuk Riset Akuntansi bagi Ikatan Akuntan Indonesia (IAI) Wilayah Sumatera Utara - Riris Rotua Sitorus; Sihar Tambun (Jurnal Pengabdian UNDIKMA, 2023)
The purpose of this community service activity is to increase the knowledge and skills of members of the Indonesian Association of Accountants regarding the use of Smart PLS software for accounting research, particularly in data processing techniques based on Structural Equation Modeling. The method of implementing this service uses training consisting of lectures and practices through zoom meeting media. The number of participants who took part in this activity were 78 (seventy-eight) participants. This service evaluation instrument uses a questionnaire via Google form. The analysis technique used was a comparison of the participants' understanding before and after attending the Smart PLS training which was analyzed descriptively. The results of this service show that there is an increase in the knowledge and abilities of the participants namely (1) the majority of participants understand how to prepare data in excel CSV and how to input data in Smart PLS. (2), the majority of participants understand how to perform validity and reliability tests with Smart PLS. (3), the majority of participants understand how to test hypotheses in the intervening research model. (4), the majority of participants understand how to test the research hypothesis on the moderating model. The skills acquired by the participants can be implemented to improve the quality and quantity of research conducted in the future.